Feasibility exploration analysis of AR virtual verification method of civil aircraft maintenance program - SUN Hongli; WANG Hongchao; ZHANG Yajie; QIAO Wanxin; ZHAO Xincan (Hangkong gongcheng jinzhan)
The difficulty of verifying civil aircraft manuals lies in the guarantee of verification resources，and there is an urgent need to develop new verification methods to achieve efficient and low-cost manual verification. An augmented reality（AR）virtual verification method based on digital model is proposed in addition to table-top verification and on-object verification methods. This paper gives the workflow of maintenance program AR virtual verification based on the technical requirements of aircraft maintenance manual verification，and explores the feasibility of this method from the perspective of building consistency with real configuration aircraft and maintenance operation consistency. Comparing the implementation requirements of on-object verification and AR virtual verification，it is demonstrated that the AR virtual verification method is feasible for the disassembly and inspection maintenance procedures.